The influence of workload and compensation on employee satisfaction - Cahyadi, Rizky; Adithio, Rafly; Santoso, Anton Budi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
It is known that many companies have succeeded in building their businesses; it's just that there is still a lack of company awareness in terms of employee welfare, especially in terms of employee job satisfaction. Employee job satisfaction can be felt from excessive workload or compensation that is not in accordance with the work they are experiencing. While employees sometimes need job satisfaction in carrying out their work in the company, this is necessary so that employees can be loyal and employees love their work more so that results can continue to be maximized, and this is a form of company achievement in treating its employees. Various aspects determine job satisfaction, both in terms of compensation and in terms of environment, workload, superiors, and colleagues. This study uses explanatory research methods where the number of respondents is 30 people, will be processed by focusing on testing the hypothesis of data analysis using statistical methods of validity testing and reliability testing using SPSS software. The following are the results of this study show that workload has an impact on job satisfaction, there is compensation for job satisfaction, and workload and compensation have a simultaneous effect on job satisfaction.